2017
DOI: 10.3390/molecules22020153
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Antibacterial Studies of N-(Benzothiazol-2-yl)-4-chlorobenzenesulphonamide and Its Neodymium(III) and Thallium(III) Complexes

Abstract: N-(Benzothiazol-2-yl)-4-chlorobenzenesulphonamide (NBTCS) was synthesized by condensation reaction of 4-chlorobenzenesulphonyl chloride and 2-aminobenzothiazole in acetone under reflux. Neodymium(III) and thallium(III) complexes of the ligand were also synthesized. Both ligand and metal complexes were characterized using UV-Vis, IR, 1H- and 13C-NMR spectroscopies, elemental analysis and molar conductance measurement. IR studies revealed that the ligand is tridentate and coordinates to the metal ions through ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Moreover, lanthanides have an interesting, but not well understood, biological role in living organisms as trace elements [ 34 ]. Our group recently reported neodymium(III) and thallium(III) complexes of N-benzothiazol-2-yl)-4-chlorobenzenesulphonamide as potential antibacterial agents [ 35 ]. Recently, Taha et al (2011) [ 36 ] reported that Nd, Dy, Sm, Pr, Gd, Tb, and Er complexes with bis-(salicylaldehyde)-1,3-propylenediimine Schiff base ligand possessed high antibacterial activity against Shigella dysenteriae , Pseudomonas aeruginosa , and Proteus vulgaris (Gram-negative bacteria).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lanthanides have an interesting, but not well understood, biological role in living organisms as trace elements [ 34 ]. Our group recently reported neodymium(III) and thallium(III) complexes of N-benzothiazol-2-yl)-4-chlorobenzenesulphonamide as potential antibacterial agents [ 35 ]. Recently, Taha et al (2011) [ 36 ] reported that Nd, Dy, Sm, Pr, Gd, Tb, and Er complexes with bis-(salicylaldehyde)-1,3-propylenediimine Schiff base ligand possessed high antibacterial activity against Shigella dysenteriae , Pseudomonas aeruginosa , and Proteus vulgaris (Gram-negative bacteria).…”
Section: Introductionmentioning
confidence: 99%
“…Metal complexes play an essential role in medicine and in agriculture (Agrawal, 2015). Metal complexes of Schiff bases possess anti-inflammatory, anti-allergic, antioxidant and analgesic, antifertility, enzymatic (Sing et al, 1999), antiproliferative (Ejidike and Ajibade, 2016) antiviral (Agrawal, 2015), and antimicrobial activity (Vasile Scăețeanu et al, 2018Vasile Scăețeanu et al, 2018, Obasi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gentamicin (C 21 H 43 N 5 O 7 ) belongs to the class of aminoglycosides and acts by preventing protein synthesis, thereby inhibiting the synthesis of nucleic acids (DNA replication or RNA synthesis) and causing death of the bacterium. Tetracycline (C 22 H 24 N 2 O 8 ) inhibits the multiplication of bacteria by binding to a subunit of the ribosomes, thereby inhibiting protein and nucleic acid synthesis and consequent death of the bacterium . Fluconazole is an antifungal drug (C 13 H 12 F 2 N 6 O) and belongs to synthetic triazoles.…”
Section: Resultsmentioning
confidence: 99%